Kajian Tentang Kecerdasan Emosi Dalam Perusahaan - Wahyudi, Wahyudi (UI Scholars Hub, 2006)
Emotional quotient determine worker’s efficacy, because it could guide the worker’s motivation in their work. Emotional quotient could guide the worker for their maximal performance, learning new skill, working with team, adaptation for changes, challenge and stress. Without emotional quotient the worker will hard to manage his emotion and relation with their colleagues. Through understanding about emotional quotient the worker could improve their ability in learning and developing their relation between their colleagues. Some experts have studied about emotional quotient, they are: Daniel Goleman, an expert in academic psychologist who explained that, emotional quotient has two competences, which is personal competence and social competence. Cooper and Sawaf mention that emotional quotient is an individual ability which is divided into four abilities, namely: emotional literacy, emotional fitness, emotional depth, and emotional alchemy. That Bahaudin, an expert in human resource management, explains a concept of human resource development named Brainware Management, this concept used emotional quotient as a measurement in efficacy of worker in their work. Bahaudin also divided emotional quotient into two competences, namely: intrapersonal and interpersonal skills.